Efficacy of vermicompost derived from local organic wastes as nursery sub-strates for cabbage and chili seedlings - Haruthai Thaisuchat; Purepan Panikanan; Jumnian Meesumlee (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study aimed to evaluate vermicompost derived from various local organic wastes as a nursery material for cultivating cabbage and chili seedlings, converting organic waste into fertilizer through vermicomposting. Method: Local organic materials, including cow dung, spent mushroom waste, and coffee grounds were utilized as the main substrates for earthworm bedding. Three main substrates, one additive (white popinac leaves), and various combinations of these materials were processed, resulting in a total of 10 methods. After two months of composting, all vermicompost was analyzed for N, P, and K content before being used as nursery material for seedling production of cabbage (Brassica oleracea) and chili (Capsicum annuum). A commercial nursery material was used as a control. Results: The results revealed a significant difference between vermicompost with bedding derived from different organic materials and N P K content. After 4 weeks of plant germination, plant height, leaf width, leaf length, and the number of leaves of cabbage showed the greatest in treatment with vermicompost 8 (cow dung: spent mushroom waste: white popinac leaves) followed by vermicompost 4 (cow dung: spent mushroom), which showed comparable results to the commercial nursery material. A negative effect on chili seedling growth was found in some treatments. Conclusion: The study concluded that cow dung proved to be an excellent material for use as a bedding substrate and earthworm feed. Vermicompost produced from a combination of cow dung and spent mushroom waste, or supplemented with white popinac leaves, can effectively serve as a nursery material for cabbage seedlings.